Wastewater treatment plant effluents in New Zealand are a significant source of microplastics to the environment - Helena Ruffell; Olga Pantos; Grant Northcott; Sally Gaw (New Zealand Journal of Marine and Freshwater Research, 2023)
Wastewater treatment plants (WWTPs) have been identified as a source of microplastics, an emerging contaminant class of increasing concern, to the environment. Three WWTPs in the Canterbury region, New Zealand, were sampled bi‐monthly from winter (June) to summer (December), to assess the variability of the abundance, morphology and polymer type of microplastics present over time. Microplastics were isolated from effluent via wet‐sieving (300 μm and 1 mm) and wet peroxide oxidation (WPO) digest, and the polymer types determined using micro‐Fourier‐Transform Infrared Spectroscopy (μ‐FTIR). Confirmed microplastics were detected at an average concentration of 1.3 ± 0.6 particles/L in effluent, with fragments comprising 58% of all morphotypes. Dominant polymer types detected were polyester, polyethylene, and polypropylene (26%, 22%, and 15%, respectively). The results of this study were comparable with those reported in international studies. An estimated 2.4 × 10 5 microplastics enter the receiving coastal environment daily from the discharge of effluent from the three WWTPs studied. No trends in microplastic concentration, morphotype and polymer type were observed in effluent samples from each WWTP, suggesting a common and continual source of microplastics into WWTPs. Further sampling is required to identify the factors that determine the variability of microplastics in WWTP influents and effluents.